2014
DOI: 10.3389/fncel.2014.00360
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine is a “find-me” signal released by neurons undergoing ethanol-induced apoptosis

Abstract: Apoptotic neurons generated during normal brain development or secondary to pathologic insults are efficiently cleared from the central nervous system. Several soluble factors, including nucleotides, cytokines, and chemokines are released from injured neurons, signaling microglia to find and clear debris. One such chemokine that serves as a neuronal–microglial communication factor is fractalkine, with roles demonstrated in several models of adult neurological disorders. Lacking, however, are studies investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…High CCL20 levels contribute to the formation of bone metastases in breast cancer [44]. CX3CL1 (also known as fractalkine or neurotactin) is a membrane-bound chemokine that can facilitate intercellular interactions, interacts with the TNFα-converting enzyme ADAM17 and is released in its shed form by apoptotic cells to recruit professional phagocytes to the site of cell death [45,46]. Fractalkine serum concentrations were higher in patients with the ER/ PR negative tumours, which is in line with the literature.…”
Section: Patient Serum and Recombinant Chemokines Lead To Reduced Barsupporting
confidence: 71%
“…High CCL20 levels contribute to the formation of bone metastases in breast cancer [44]. CX3CL1 (also known as fractalkine or neurotactin) is a membrane-bound chemokine that can facilitate intercellular interactions, interacts with the TNFα-converting enzyme ADAM17 and is released in its shed form by apoptotic cells to recruit professional phagocytes to the site of cell death [45,46]. Fractalkine serum concentrations were higher in patients with the ER/ PR negative tumours, which is in line with the literature.…”
Section: Patient Serum and Recombinant Chemokines Lead To Reduced Barsupporting
confidence: 71%
“…Moreover, rats treated with acute ethanol displayed a decrease in CXCL12 levels after 4 h, which is congruent with the data from repeated experiments. Regarding plasma CX 3 CL1, most studies on the effects of alcohol are focused on the CNS (30, 31) and pancreas (32, 33) but a recent study has reported elevated concentrations of CX 3 CL1 in the serum of mice treated chronically (5 months) with ethanol (26), which is in opposition to our data in AUD patients but compatible with our preclinical data since ethanol-treated rats had higher plasma CX 3 CL1 concentrations, especially in rats acutely treated. However, it is important to indicate that species, doses and intensity of the exposure were not comparable in between these studies and that further research is needed to understand the time-course of the changes in chemokines in plasma after acute and chronic alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the activation of microglia in the diabetic brain may contribute to inflammatory injury has not been fully investigated, although the microglia activation pathway in the hypothalamus has been documented in diabetes [85]. Stress signals that induce inflammasome formation include chemokines and damage-associated molecular patterns, such as the high mobility group proteins HMGB1 and ATP [8688]. For the therapeutic targeting of inflammasome formation induced by mitochondrial injury, sirtuins appear to show promise [89, 90].…”
Section: Mitochondrial Dysfunction and Inflammasome Formationmentioning
confidence: 99%